Humanized Islamic Leadership dalam Penanganan Burnout Santri di Era Digital - Zema Yuliana Aulan; Muhammad Edi Jayadi; Muhammad (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study aims to analyze the implementation of Humanized Islamic Leadership in addressing student burnout in the digital era at Pondok Pesantren Al-Aziziyah. The phenomenon of student burnout is influenced by academic pressure, the dynamics of boarding school life, and the intensity of digital technology use, which affect students’ emotional, mental, and spiritual conditions. This research employed a qualitative method with a descriptive phenomenological approach. Data were collected through participatory observation, in-depth interviews, documentation, and questionnaires involving Islamic boarding school leaders, teachers, dormitory supervisors, and students. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing using an interactive analysis model. The findings reveal that student burnout is primarily caused by three factors: academic workload, socio-cultural pressures within boarding school life, and digital culture distractions that lead to digital fatigue. The study further demonstrates that the implementation of Humanized Islamic Leadership through dialogic communication, empathetic approaches, spiritual guidance, and emotional mentoring strengthens students’ psychological resilience and creates psychological safety within the boarding school environment. This study contributes to the development of Islamic educational management by integrating humanism, spirituality, and digital literacy as strategies for addressing student burnout in the digital era.